2016
DOI: 10.1021/acs.energyfuels.6b01430
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Quantification of Thermally Induced Porosity Alteration of Immature Source Rock Using X-ray Computed Tomography

Abstract: This paper summarizes results of a successful laboratory investigation to visualize and quantify pyrolysis-induced porosity evolution of Uinta Basin organic-rich source rock using X-ray computed tomography (CT). Combining CT imaging techniques with a radio-opaque gas as a pore contrast fluid allowed for the description of porosity changes within source rock rather than limiting quantification to a single bulk value, as obtained by conventional porosity measurement techniques. The porosity of the immature and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Moreover, organic rich specimens that have been thermally decomposed under confinement in the laboratory, or natural samples studied by microstructural analyses [Kalani et al, 2015], have revealed fractures filled with mobile organic matter. Laboratory experiments also suggested that kerogen transformation leads to the formation of fractures whose propagation direction (predominantly sub-parallel to the bedding plane) are controlled by the anisotropic stress and rock mechanical properties (strength and toughness), and by the orientation of kerogen patches in the source rock [Vernik, 1994;Kobchenko et al, 2011;Glatz et al, 2016]. In comparison with a previous study [Panahi et al, 2012], the rate of temperature increase, before the sample was held at a constant temperature, was slower.…”
Section: Mechanisms Of Primary Migrationmentioning
confidence: 93%
“…Moreover, organic rich specimens that have been thermally decomposed under confinement in the laboratory, or natural samples studied by microstructural analyses [Kalani et al, 2015], have revealed fractures filled with mobile organic matter. Laboratory experiments also suggested that kerogen transformation leads to the formation of fractures whose propagation direction (predominantly sub-parallel to the bedding plane) are controlled by the anisotropic stress and rock mechanical properties (strength and toughness), and by the orientation of kerogen patches in the source rock [Vernik, 1994;Kobchenko et al, 2011;Glatz et al, 2016]. In comparison with a previous study [Panahi et al, 2012], the rate of temperature increase, before the sample was held at a constant temperature, was slower.…”
Section: Mechanisms Of Primary Migrationmentioning
confidence: 93%
“…Certain experiments, however, stand to benefit greatly from increased exposure times as noise is decreased. The noise reduction gives rise to better statistics if, for example, porosity is to be estimated in combination with a non-wetting radio contrast agent [ 9 ]. Similarly, core flood experiments necessitate the presence of a vessel to maintain temperatures and pressures resulting in attenuation of the X-rays.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the variation of macroscopic rock properties after high-temperature heat treatment and achieved some progress. Regarding the pore structure, various experimental techniques, including CT scanning electron microscope (CT-SEM) [15], mercury intrusion porosimetry (MIP) [16][17][18][19][20], micro-CT [21,22], field emission scanning electron microscopy (FE-SEM) [23,24], low-field nuclear magnetic resonance (NMR) [25], photoacoustic spectrometry (PAS) [26], ultrasonic velocity measurement (UVM) [27], etc., were used to study the high-temperature effects on the porosity, pore size, and pore morphology of various materials such as calcareous sediments [21], coal [15,25], concrete [16], shale [22][23][24], granite [28,29], sandstone [18,19,28], limestone [17,20], and carbonate [27]. Almost all of the above studies have shown that thermal damage and microcracks are induced by high temperature and the rock porosity and permeability gradually increase with temperature, while the pore fractal dimension decreases.…”
Section: Introductionmentioning
confidence: 99%